What antimicrobial stewardship strategies do NHS commissioning organizations implement in primary care in England?. Issue 2 (14th May 2020) - Allison, Rosalie; Lecky, Donna M; Beech, Elizabeth; Costelloe, Céire; Ashiru-Oredope, Diane; Owens, Rebecca; McNulty, Cliodna A M
Abstract: Objectives: To identify and explore strategies that English NHS commissioning organizations implemented to improve antimicrobial stewardship (AMS) within primary care. Methods: Questionnaire sent to the medicines management teams (MMTs) of all 209 clinical commissioning groups (CCGs) in England, in 2017. Results: A total of 89% (187/209) of all English CCGs responded to the questionnaire; 74% of responding CCGs (123/167) had a prescribing incentive/engagement scheme, with MMTs representing 88% (90/102) considering incentive schemes successful or very successful for prioritizing AMS in primary care, especially when linked to prescribing NHS Quality Premium indicators. AMS audits were considered successful or very successful by 91% (126/138) of responding CCGs, as they identify reasons for inappropriate prescribing and opportunities for future improvement. All responding MMTs (169/169 CCGs) reported feeding back local/national antimicrobial prescribing data to the general practices they commission, 85% (142/168) to their CCG/Commissioning Support Unit (CSU) board and only 33% (56/169) to out-of-hours services. Benchmarking prescribing data was reported as a powerful tool to engage practices, facilitating an element of competition and peer pressure. Conclusions: National antimicrobial resistance improvement schemes, in particular the NHS England Quality Premium, have influenced CCG improvement priorities. Most CCGs now report successful improvement strategies including the use of both local and national antibiotic prescribing data to motivate improvements; these should be continued and extended to out-of-hours providers. As local audit data have helped to identify reasons for inappropriate prescribing and inform improvement planning, all organizations should adopt this strategy and include it in local quality improvement schemes, ensuring performance reporting to organizational board level.